Lift-the-Flap Book Media to Improve Pancasila Education Learning Outcomes in Elementary School - Adiesti Peppy Ramadhani; Susilo Tri Widodo (Journal of Education Reseach and Evaluation, 2024)
The lack of learning media impacts student learning outcomes and low learning motivation. Based on this, this study aimed to develop and test the feasibility and effectiveness of lift-the-flap book media to improve learning outcomes of Pancasila Education. This type of research uses the Borg & Gall development model by simplifying 8 of the ten stages: potential and problems, data collection, media design, design validation, design revision, initial trial, product revision, and trial use. The research subjects were one learning media expert and one learning material expert. The test subjects were teachers and 27 fourth-grade students. The methods used to collect data are observation, interviews, documentation, and questionnaires and tests. The instruments used to collect data are questionnaires and test questions. The techniques used to analyze the data were qualitative descriptive analysis and quantitative and inferential statistics. The study results are media and material validity, with very feasible categories of teacher and student responses in the exciting category. The t-test results show a difference in the average results between the pretest and post-test. It is concluded that the lift-flap-book media effectively improves Pancasila Education learning outcomes.